2013
DOI: 10.1093/humrep/det321
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: new candidates for the regulation of the human cumulus–oocyte complex

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 68 publications
5
70
1
4
Order By: Relevance
“…To our knowledge, this is the first human study to characterize global miRNA expression in FF according to the degree of maturation of the oocyte retrieved while also excluding pathologies that could potentially bias the miRNA profile. Different studies have focused on characterizing FF miRNAs from patients with different reproductive pathologies such as premature ovarian failure (POF) or PCOS (20,21,40) in cumulus cells obtained from uncharacterized IVF patients or unfertilized oocytes (41). However, the presence of such pathologies could represent a source of bias since the role of different miRNAs has already been related to diverse genital tract dysfunctions (42).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first human study to characterize global miRNA expression in FF according to the degree of maturation of the oocyte retrieved while also excluding pathologies that could potentially bias the miRNA profile. Different studies have focused on characterizing FF miRNAs from patients with different reproductive pathologies such as premature ovarian failure (POF) or PCOS (20,21,40) in cumulus cells obtained from uncharacterized IVF patients or unfertilized oocytes (41). However, the presence of such pathologies could represent a source of bias since the role of different miRNAs has already been related to diverse genital tract dysfunctions (42).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown that miRNA may play an important role in female fertility and in the regulation of oocyte and CC crosstalk (Mishima et al, 2008;Assou et al, 2013;Donadeu and Schauer, 2013;Velthut-Meikas et al, 2013). However, to the best of our knowledge, no study has tested the involvement of other noncoding RNAs in folliculogenesis and ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…The maturation, development and quality of oocytes are provided through cumulus cells by growth factors, paracrine signals, secondary messenger and nutrient exchanges [3,5,17,22,37,41]. In addition, cumulus cells are involved in extracellular matrix and apoptosis via microRNAs (MIR29a, MIR30d, MIR21, MIR93, MIR320a, MIR125a and the LET7 family) [7].…”
Section: Introductionmentioning
confidence: 99%